2021
DOI: 10.1111/ijd.15414
|View full text |Cite
|
Sign up to set email alerts
|

Skin manifestations in COVID‐19 patients, state of the art. A systematic review

Abstract: Introduction Since COVID‐19 has become a pandemic, extensive literature has been produced. The commonest symptoms of COVID‐19 disease are fever, cough, anosmia, and lymphocytopenia. However, other apparently less common clinical symptoms have been described, including skin lesions. We conducted a systematic review to evaluate skin involvement in COVID‐19. Methods The authors performed a systematic review of literature, in accordance with the Preferred Reporting Items fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 59 publications
(128 reference statements)
3
33
0
1
Order By: Relevance
“…The onset of vesicular lesions is usually later than that of SARS-CoV-2 disease symptoms, with a latency time of 14 days occurring more frequently in middle-aged patients [20]. However, according to other studies [30,33], these lesions appeared earlier than other clinical manifestations of COVID-19 in 72.5% of cases and were associated with a medium severity of SARS-CoV-2 infection. In this way, Jindal et al [31] reported that vesicular lesions occur in the early stages of COVID-19, even before the onset of fever and cough, and last about 10 days.…”
Section: Vesicular Eruptionsmentioning
confidence: 85%
See 1 more Smart Citation
“…The onset of vesicular lesions is usually later than that of SARS-CoV-2 disease symptoms, with a latency time of 14 days occurring more frequently in middle-aged patients [20]. However, according to other studies [30,33], these lesions appeared earlier than other clinical manifestations of COVID-19 in 72.5% of cases and were associated with a medium severity of SARS-CoV-2 infection. In this way, Jindal et al [31] reported that vesicular lesions occur in the early stages of COVID-19, even before the onset of fever and cough, and last about 10 days.…”
Section: Vesicular Eruptionsmentioning
confidence: 85%
“…In COVID-19, the prevalence of vesicular lesions is 15%, identifying a diffuse pattern in 75% and a localized pattern in 25% of patients [29]. Perna et al [30] described a prevalence of 12.5%, while according to a series of cases analyzed by Singh et al [22]-this percentage varies between 3.7% and 15%. These lesions occur more frequently in adults, most of them male (72.7%).…”
Section: Vesicular Eruptionsmentioning
confidence: 99%
“…There are two published cases of urticarial vasculitis [66]. However, a couple of systematic reviews have pointed out that most cutaneous manifestations could be traced to various drugs the patients were on [67,68]. The cause of purpura could be traced to thrombosis in several cases, and these would usually appear early in the disease onset.…”
Section: Rheumatic Manifestations In Covid-19mentioning
confidence: 99%
“…The limbs seem to be more frequently involved than trunk and face. [8] Male-to-female ratio of 1 : 9 has been found in several studies. Chilblains are typical feature of COVID-19, very common amongst the skin lesions and are seen in almost half of all cases with skin lesions.…”
Section: Role Of Dermatologists In Covid-19 Pandemicmentioning
confidence: 85%
“…Recently cases of Kawasaki disease in children are increasingly being reported. [8] Recently it has been suggested that cryofibrinogenemia might be an important pathogenic factor for the development of chilblains related to COVID-19. [9] Chilblains, purpuric lesions, livedo reticularis, cyanosis, Raynaud's phenomenon, acral blisters, and ulceration are common clinical manifestations of cryofibrinogenemia as such.…”
Section: Role Of Dermatologists In Covid-19 Pandemicmentioning
confidence: 99%